One‐Pot Two‐Step Microwave‐Assisted Synthesis of Alkylidene Acetoacetamido Esters, Useful Intermediates for β‐Dehydropeptides. Issue 19 (13th June 2016) - Viola, Angelo; Ferrazzano, Lucia; Greco, Roberto; Cerisoli, Lucia; Caldi, Jonathan; Tolomelli, Alessandra
Abstract : Alkylidene acetoacetamides are useful building blocks for the preparation of a number of biologically active derivatives, including dehydro‐β‐amino‐acid‐containing peptidomimetics. A one‐pot two‐step protocol for the preparation of amino‐acid‐derived unsaturated acetoacetamides has been optimized. The use of microwave activation avoids, or at least decreases, the need for catalysts in both steps. A leucine derivative was selected from the small collection of molecules obtained to be transformed into the corresponding dehydro‐β‐amino‐acid‐containing peptidomimetic. It is known that such fragments are able to induce β‐turns into peptide sequences, and, due to the presence of the unsaturation, they may represent sites for selective modification and conjugation. Abstract : A one‐pot two‐step synthesis of amino‐acid‐derived unsaturated acetoacetamides is reported. The use of microwave activation avoids, or at least decreases, the need for catalysts in both steps. Alkylidene are useful building blocks for the preparation of dehydro‐β‐amino‐acid‐containing peptidomimetics.